PENGENDALIAN KUALITAS PRODUK BERBASIS TOTAL QUALITY MANAGEMENT (TQM) DALAM MENINGKATKAN DAYA SAING INDUSTRI MIE INSTAN DI INDONESIA - Joanna Brigitta S; Paskah Gloria S. Sipahutar; Dionisius Sihombing; Melati Sihombing; Siti Agriyani; Zazira Safwa Syahfitri Bangun (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Indonesia ranks second in global instant noodle consumption, reaching 14.26 billion servings in 2022, making product quality control a central concern for industry players. This study examines how Total Quality Management (TQM) principles are applied within Indonesia’s instant noodle industry and their relation to maintaining competitive advantage. A literature review method was used with a qualitative descriptive approach and content analysis of relevant academic sources. The study found that applying seven TQM elements, namely top management commitment, customer orientation, continuous improvement, employee involvement, production process control, supplier relationship management, and data-based decision making, contributes meaningfully to production efficiency, defect reduction, consumer trust, and global market competitiveness. This study offers a conceptual framework linking TQM, Quality Control, and Competitiveness specifically within the Indonesian instant noodle industry context, an area that has received relatively limited academic attention. Keywords: Total Quality Management (TQM), Quality Control, Industrial Competitiveness